The rs1256328 (ALPL) and rs12654812 (RGS14) Polymorphisms are Associated with Susceptibility to Calcium Nephrolithiasis in a Taiwanese population - Chen, Wei-Chiao; Chou, Wan-Hsuan; Chu, Hou-Wei; Huang, Chi-Chen; Liu, Xiao; Chang, Wei-Pin; Chou, Yii-Her; Chang, Wei-Chiao (Scientific reports, 2019)
Nephrolithiasis is a common disease affecting almost all populations, with an increasing prevalence over the past decades. Previous studies revealed several functional polymorphisms associated with the pathogenesis of nephrolithiasis. However, data on Asian populations are limited. In this study, three candidate polymorphisms were selected from previous studies to investigate the correlations with nephrolithiasis in a Taiwanese population. In total, 454 nephrolithiasis patients were recruited from Kaohsiung Medical University Hospital, with SNP frequency for 1513 subjects of general population from the Taiwan Biobank (TWB) as a genotypic reference. Results revealed that subjects with minor TT genotype at rs1256328 ( alkaline phosphatase, liver/bone/kidney ( ALPL )) have higher susceptibility to nephrolithiasis (odds ratio (OR) = 2.03, p = 0.0013). In addition, subjects carrying the minor AA genotype at rs12654812 ( regulator of G protein signaling 14 (RGS14) ) have higher susceptibility to nephrolithiasis (OR = 1.91, p = 0.0017). Among nephrolithiasis patients, subjects with GG at rs7627468 ( calcium-sensing receptor ( CASR )) have lower pH level in urine ( p = 0.0088). Importantly, rs7627468 is associated with the expressions of IQCB1 and EAF2. rs12654812 could influence the expression of RGS14 itself, MXD3 , and FGFR4 . In summary, this study successfully validated the genetic roles of rs1256328 and rs12654812 in human nephrolithiasis.